O vampirismo feminino em Carmilla e suas reverberações - Correa, Bruna Pascoal (2022)
The present research focuses on unraveling the figure of the vampire in the gothic novel Carmilla, (1872), by Sheridan Le Fanu, composed by the roots of the vampiric myth intertwined with the image of the feminine. The dissertation uses quantitative methodology, performing readings and analysis of selected theoretical and literary texts, so that the traced object can be theoretically grounded. The chosen narrative has as antagonist the vampire Carmilla, who names the novel, and to understand her construction as a meta-empirical figure, an investigation will be carried out on the sociocultural context, together with the conditions of existence of women in the 19th century, period of publication of the novel. In addition, we will deal with the contributions of the Gothic and the fantastic in the narrative and, consequently, for the existence of the antagonist character. Finally, with the objective of briefly analyzing the reverberations of the female vampiric myth, emerging the importance of the figure not only in the 19th century, the work examines other female vampiric figures, more specifically, the character Cláudia, represented in the novel Interview with the Vampiro (1976) in counterpoint to Carmilla (1872). At the end of the research, erasure and one-sidedness were found to be the position of the vampire woman, often being considered only as seductive and cunning, not apprehending the other various nuances within her constitution, such as, for example, the contradictoriness of symbols that this unusual figure carries within itself.